FEASIBILITY STUDY OF GROUPER FISH PROCESSING INDUSTRY IN JAVA ISLAND BASED ON RAW MATERIAL AVAILABILITY ANALYSIS - Ulil Albab, Alif Rizki; Asiyah Wardah, Siti Nur; At-Ta'anny, Ummu (Jurnal Teknologi Industri Pertanian, 2025)
Grouper is a high-value fishery commodity with increasing demand in both domestic and international markets, necessitating a stable raw material supply to support sustainable processing activities. However, feasibility assessments for developing grouper processing industries in Indonesia rarely prioritize raw material availability, despite this factor being essential for maintaining consistent production. This study evaluates the feasibility of establishing a grouper processing industry in Java by integrating cross-regional supply mapping with an inventory control analysis based on the Safety Stock (SS) and Reorder Point (ROP) approaches. A mixed-methods design was used, combining semi-structured interviews, field observations at ten major supply points along the northern coast of Java, and analysis of twelve months of supply and demand data. Findings indicate that the total monthly grouper supply reaches approximately 254 tons, while industrial requirements are around 50 tons. Cold chain capacity, logistics conditions, and the distance of distribution influence price differences across regions. Seasonal fluctuations can be managed by relying on both capture fisheries and floating net cage aquaculture, which help maintain a consistent supply throughout the year. A simulation using an SS value of 602 kilograms and an ROP value of 2,402 kilograms demonstrated that no stock outs occurred during a ten-day evaluation. Overall, the study confirms that the supply of grouper raw materials in Java is stable, feasible, and capable of supporting the growth of processing industries, providing a practical basis for future supply chain planning. These findings offer guidance for policymakers and industry stakeholders nationwide. Keywords: grouper supply chain, raw-material feasibility, inventory control, safety stock, reorder point